Characterization of Strip1 Expression in Mouse Cochlear Hair Cells - Zhang, Shasha; Dong, Ying; Qiang, Ruiying; Zhang, Yuan; Zhang, Xiaoli; Chen, Yin; Jiang, Pei; Ma, Xiangyu; Wu, Leilei; Ai, Jingru; Gao, Xia; Wang, Pengjun; et al. (Frontiers in Genetics, 2021)
Striatin-interacting protein 1 (Strip1) is a core component of the striatin interacting phosphatase and kinase (STRIPAK) complex, which is involved in many important processes, such as embryogenesis and development, circadian rhythms, type 2 diabetes, and cancer progression. However, the expression and role of Strip1 in the mammalian cochlea remains unclear. Here we studied the expression and function of Strip1 in the mouse cochlea by using Strip1 knockout mice. We first found that the mRNA and protein expression of Strip1 increases as mice age starting from postnatal day (P) 3 and reaches its highest expression level at P30. We also found that the expression of Strip1 can be detected by immunofluorescent staining starting from P14 only in cochlear HCs, but not in supporting cells (SCs). Next, we crossed Strip1 heterozygous knockout (Strip+/−) mice to obtain Strip1 homozygous knockout (Strip1−/−) mice for studying the role of Strip1 in cochlear HCs. However, no Strip1−/− mice were obtained and the ratio of Strip1+/− to Strip1+/+ mice per litter was about 2:1, which suggested that homozygous Strip1 knockout is embryonic lethal. We measured hearing function and counted the HC number in P30 and P60 Strip1+/− mice and found that they had normal hearing ability and HC numbers compared to Strip1+/+ mice. Our study suggested that Strip1 probably play important roles in HC development and maturation, which needs further study in the future.